Dialogical Social Theory - Levine, Donald N.; Schneiderman, Howard G. (London : Taylor and Francis, 2018)
"In his final work, Donald N. Levine, one of the great late-twentieth-century sociological theorists, brings together diverse social thinkers. Simmel, Weber, Durkheim, Parsons, and Merton are set into a dialogue with philosophers such as Hobbes, Smith, Montesquieu, Comte, Kant, and Hegel and pragmatists such as Peirce, James, Dewey, and McKeon to describe and analyze dialogical social theory. This volume is one of Levines most important contributions to social theory and a worthy summation of his lifes work.Levine demonstrates that approaching social theory with a cooperative, peaceful dialogue is a superior tactic in theorizing about society. He illustrates the advantages of the dialogical model with case studies drawn from the French Philosophes, the Russian Intelligentsia, Freudian psychology, Ushibas aikido, and Levines own ethnographic work in Ethiopia. Incorporating themes that run through his lifetimes work, such as conflict resolution, ambiguity, and varying forms of social knowledge, Levine suggests that while dialogue is an important basis for sociological theorizing, it still vies with more combative forms of discourse that lend themselves to controversy rather than cooperation, often giving theory a sense of standing still as the world moves forward.The book was nearly finished when Levine died in April 2015, but it has been brought to thoughtful and thought-provoking completion by his friend and colleague Howard G. Schneiderman. This volume will be of great interest to students and teachers of social theory and philosophy."--Provided by publisher.
part, I From Combat to Dialogue / Donald N. Levine -- chapter Dialogue, Disputation, Dismissiveness and the Motives for Controversy / Howard G. Schneiderman -- chapter 1 Dialogical Social Theory / Donald N. Levine -- chapter 2 Dialogue and Human Combat / Donald N. Levine -- chapter 3 Transforming the Adversarial Mindset -- Japanese Martial Arts and American Litigation / Donald N. Levine -- chapter 4 Civilizations, Clashing and Harmonious / Donald N. Levine -- part, II Dialogue Involving Shared Objectives / Donald N. Levine -- chapter 5 Universalism in the French Philosophes and the Russian Intelligentsia / Donald N. Levine -- chapter 6 The Sociology of Morality in the Work of Parsons, Simmel, and Merton / Donald N. Levine -- chapter 7 Theory and Praxis in Parsons and McKeon / Donald N. Levine -- chapter 8 Freud and Ueshiba -- Pioneers of Therapeutic Human Interaction / Donald N. Levine -- chapter 9 Dewey and Hutchins at Chicago / Donald N. Levine -- part, III Dialogues Involving Pointed Conversations / Donald N. Levine -- chapter 10 Hobbes and Locke / Donald N. Levine -- chapter 11 Montesquieu and Durkheim / Donald N. Levine -- chapter 12 Kant and Hegel / Donald N. Levine -- chapter 13 Positions on Conflict in Euro-American and Asian Social Thought / Donald N. Levine -- chapter 14 Two Tales of one City / Donald N. Levine -- chapter 15 The Forms and Functions of Social Knowledge / Donald N. Levine.
Keywords: Social policy; Social sciences -- Philosophy; Sociology; Classical Social Theory; Philosophy of Social Science; Social Theory; Sociology & Social Policy